Margin Laba Bersih dan Perilaku Pemegang Saham Mayoritas Terhadap Pergerakan Harga Saham Pada Ex-Dividend Date - Deni Ramdani (AFRE (Accounting and Financial Review), 2021)
This study aims to analyze how long the duration of the increase in stock prices in order to return to a minimum, such as stock prices on the cum-dividend date, whether changes in net profit margin affect stock prices ex-dividend date. movement, then whether the majority shareholder influences the price movement. The ex-dividend date of the current stock. The research sample used a purposive sampling method, namely the determination of samples with special criteria referring to companies registered in LQ 45 for the 2017-2019 period. Thus it can be interpreted that the Net Profit Margin and the majority shareholder together have no significant effect on stock price movements on the ex-dividend date. From the results of the study it was concluded that the net profit margin and the majority shareholder had no significant effect on stock price movements on the ex-dividend date.